Analisis Sintaksis Majrurat Al-Asma Dalam Surat Yasin - Rahmawati, Rima Ajeng; Khairil Anwar (An Naba, 2022)
Majrurat al-asma is part of the material contained in Arabic grammar. It is still rarely discussed and indicated by the fact that many Arabic students only know that majrur only caused by the inclusion of the letter jar and the sign of majrur is only kasroh, even though there other reasons for majrur are being idhofah and caused to being tawabi'. There are other signs of majrur not only kasrah but also ya and fathah as a substitute for kasroh. The research on majrurat al-asma has been widely used as a tool in researching Arabic, both in studying ancient manuscripts and Surahs of the Qur'an. While the researchers themselves want to study more about majrurat al-asma, one of Surah in the Qur'an is Surah Yasin. Surah Yasin is the 36th surah of the Quran and was revealed in the middle period in Mecca (before the hijrah), so it belongs to the Makkiyah surah group. This surah consists of 83 verses. However, the fact that it happened in Indonesia found that Yasin was the most frequently read letter after Al-Fatihah, Al-Ikhlas, Al-Falaq, and An-Nas. The research is a library research. The literature study in question is trying to study linguistic theory or linguistic studies. Where researchers browse, analyze data through the literature. The results of this study indicate that The signs of I'rob jar in the Al-Qur'an letter Yasin include: Kasroh which consists of isim mufrod 69 data, jama’ taksir 13 and jama’ muannas salim 1 data. Ya there are 3 data. Fathah amounted to 1 data. In the form of masdar muawwal 1 data, isim maushul 7 data and 69 legal data are mabni. Keywords: Majurat al-asma, Arabic Grammar, Surah Yasin